Effect of Different Additional Foods on the Growth of Nila Fish (Oreochormis niloticus) - Khusnul Khotimah; Meika Puspita Sari; Amin Uswatun Hasanah (Universitas Muhammadiyah Palembang, 2023)
This research aims to see and study the effect of the addition of several types of feed ingredients on the growth response of tilapia (Oreochormis niloticus). This research was conducted at the Aquaculture Laboratory, Faculty of Agriculture, University of Muhammadiyah Palembang. This research used experimental with a completely randomized design (CRD) of 3 treatments and 6 replicates. The feed additives used in this study were P1 (Moringa leaf extract), P2 (Bean sprout extract), and P3 (Lamtoro leaf extract). From observations made for 60 days and sampling every 10 days, the results of observations of tilapia reared with the addition of P1 feed, namely Moringa leaf flour mixed with pellets, showed the highest growth results compared to other treatments. Meanwhile, the lowest growth value was shown by the P3 treatment, namely lamtoro leaf flour mixed with pellets. The conclusion is that the best feed additive for red tilapia growth is the addition of a lamtoro flour mixture.